(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2021)
A Taguchi-based design of experiments was employed to optimize fast-dissolving tablet formulations of domperidone using three starches from banana (Musa acuminata), cassava (Manihot esculenta) and Chinese yam (Dioscorea rotundata). The starches were modified by carboxymethylation (degree of substitution 0.32±0.02) and used as superdisintegrants (2–8%w/w), in comparison to sodium starch glycolate (SSG). Effects of two variables (superdisintegrant type and superdisintegrant concentration) at four levels on crushing strength-friability ratio (CSFR), disintegration time (DT) and dissolution time to 80% drug release (t80) were analyzed. Domperidone tablets containing carboxymethylated starches had higher CSFR values (p<0.05) than SSG while DT and t80 decreased with concentration. Taguchi’s delta values and analysis of variance showed that superdisintegrant type had greater influence on CSFR and t80 while superdisintegrant concentration had greater influence on DT. Optimum fastdissolving domperidone tablets were obtained using 2% w/w Chinese yam starch (CSFR= 251.25±16.32) and 8% w/w SSG (DT = 0.42±0.03 min; t80 = 0.50±0.02 min).